Static Friction Coefficient into Cylindrical Joints Assemblies - A. Todi-Eftimie; S. Bobancu; C. Gavrila; L. Eftimie (Tribology in Industry, 2015)
The aim of this research is to analyze the behavior of the transition between static and dynamic friction coefficient in a cylindrical joint, in order to reach high reliability when loads are acting. The friction between cylindrical contact faces is analyzed both in dry and lubricated conditions up to the moment that the assembly starts moving while tilting the entire assembly. It means that it is analyzed a complex static friction developed along a chain and its sprocket.